Pengaruh Kualitas Sistem, Informasi dan Layanan Terhadap Kepuasan Pengguna dalam Menentukan Net Benefit Seller UMKM (Studi Kasus pada Toko Online Shopee Indonesia) - Raden Ayu Syarifa; Riauli Susilawaty (Indonesian Accounting Literacy Journal, 2021)
Shopee is the most widely used e-commerce by Indonesians and its existence is expected to provide convenience in trade transactions that will benefit its sellers. This research aims to determine the influence of system quality, information quality and service quality on user satisfaction in determining the net benefit of MSME seller by using the DeLone and McLean approach as a model to measure the success of an information system. This study uses structural equation modeling (SEM) statistical methods with smartpls 3.0 applications. The results prove that The Quality of Information and Quality of Services have a positive and significant effect on User Satisfaction, while System Quality has a positive but insignificant effect on User Satisfaction. User Satisfaction has a positive and significant effect on Net Benefit.